Effect Of Different Filler Preparation Method On Properties Of Natural Rubber Palygorskite Nanocomposites - Muttalib, Siti Nadzirah Abdul (2017)
Recently, clay has been widely used as fillers to enhance properties in polymer nanocomposites at lower filler loading. However, the improvement of the properties depends on the ability of the clay to disperse in the polymer matrix. In this study, the mechanical, morphological and physical properties of nanocomposites containing natural rubber (NR) and palygorskite (PAL) prepared by combining latex coagulation and melt mixing method were investigated. In attempts to prepare nanofillers with enhance compatibility with polymer matrix, different types of filler preparation method were applied (ball milling and cation exchange). The effect of different ball milling parameters on NR/PAL nanocomposites was investigated to prepare homogenous PAL dispersion. PAL also was prepared by treated using cation exchange method. The composites were subjected to curing characteristics, tensile properties, tear strength, hardness, swelling, fourier transform infrared spectroscopy (FTIR), x-ray diffraction analysis (XRD), scanning electron microscopy (SEM), transmission electron spectroscopy (TEM) and dynamic mechanical analysis (DMA) test. It was found that NR/PAL nanocomposites with ball milling parameters of 5:1 ratio using large size ball mills (35 mm) and treated with octadecylamine (ODA) have improved mechanical, morphological and physical properties compared to untreated composites. These nanocomposites have higher tensile properties, high crosslink density and lower rubber-filler interaction.